UPAYA MENERAPKAN NILAI-NILAI TOLERANSI BUDAYA PADA SISWA KELAS VIII MTsN 1 MEDAN - Putri, Emilia; Nasution, Toni; Nirwana, Retno Dwi Bella; Salsabila, Ririn (Yayasan Pendidikan Islam Akmalia, 2022)
Multicultural embraces a cultural diversity within a region of diverse both traditional and modern societies. With a background determined by social, racial, ethnic, mores, gender, and religion. Cultural diversity will always affect the way humans think, behave, and behave. Multicultural education can be a tool in developing insight, knowledge, and the cultivating of tolerance. Multicultural education comes from a society that is beginning to appreciate the importance of valuing each other's ethnic, national, language, and cultural differences. Teachers are the subjects that have played a major role in the implanting of multicultural core values such as democracy, humanism, and pluralism